Ultrasound enhances calcium absorption of jujube fruit by regulating the cellular calcium distribution and metabolism of cell wall polysaccharides. (1st June 2017) - Zhi, Huanhuan; Liu, Qiqi; Xu, Juan; Dong, Yu; Liu, Mengpei; Zong, Wei
Abstract: BACKGROUND: Ultrasound has been applied in fruit pre‐washing processes. However, it is not sufficient to protect fruit from pathogenic infection throughout the entire storage period, and sometimes ultrasound causes tissue damage. The goal of this study was to investigate the effects of calcium chloride (CaCl2, 10 g L −1 ) and ultrasound (350 W at 40 kHz), separately and in combination, on jujube fruit quality, antioxidant status, tissue Ca 2+ content and distribution along with cell wall metabolism at 20 °C for 6 days. RESULTS: All three treatments significantly maintained fruit firmness and peel color, reduced respiration rate, decay incidence, superoxide anion, hydrogen peroxide and malondialdehyde and preserved higher enzymatic (superoxide dismutase, catalase and peroxidase) and non‐enzymatic (ascorbic acid and glutathione) antioxidants compared with the control. Moreover, the combined treatment was more effective in increasing tissue Ca 2+ content and distribution, inhibiting the generation of water‐soluble and CDTA‐soluble pectin fractions, delaying the solubilization of Na2 CO3 ‐soluble pectin and having lower activities of cell wall‐modifying enzymes (polygalacturonase and pectate lyase) during storage. CONCLUSION: These results demonstrated that the combination of CaCl2 and ultrasound has potential commercial application to extend the shelf life of jujube fruit by facilitating Ca 2+ absorption and stabilizing the cell wall structure. © 2017 Society of Chemical Industry